2016
DOI: 10.1111/cea.12695
|View full text |Cite
|
Sign up to set email alerts
|

Role of local eosinophilopoietic processes in the development of airway eosinophilia in prednisone‐dependent severe asthma

Abstract: Patients with severe eosinophilic asthma have an exaggerated eosinophilopoeitic process in their airways. Treatment with 100 mg subcutaneous mepolizumab significantly attenuated systemic differentiation of eosinophils, but did not suppress local airway eosinophil differentiation to mature cells. Targeting IL-5-driven eosinophil differentiation locally within the lung maybe of relevance for optimal control of airway eosinophilia and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 41 publications
2
101
0
1
Order By: Relevance
“…While anti-IL-5 therapies reduce the occurrences of asthma exacerbations in severe eosinophilic asthma[3, 4], airway eosinophil precursors remain mostly unaffected by these therapies [54-56]. We and others previously showed that IL-5 receptor α is downregulated on IL-5-activated blood eosinophils as well as airway eosinophils obtained after airway allergen challenge [11-13].…”
Section: Discussionmentioning
confidence: 99%
“…While anti-IL-5 therapies reduce the occurrences of asthma exacerbations in severe eosinophilic asthma[3, 4], airway eosinophil precursors remain mostly unaffected by these therapies [54-56]. We and others previously showed that IL-5 receptor α is downregulated on IL-5-activated blood eosinophils as well as airway eosinophils obtained after airway allergen challenge [11-13].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil-lineage committed cells have also been identified in lung tissue in a mouse model of allergic airway inflammation (26). More recently, eosinophil progenitors isolated from the blood of patients with severe eosinophilic asthma have been shown to have an exaggerated clonogenic response to IL-5 in vitro , compared to eosinophil precursors from mild asthmatics, suggesting that in situ eosinophilopoiesis may have a clinically relevant role in severe eosinophilic asthma (27). …”
Section: Eosinophil Differentiation Maturation Migration Activatiomentioning
confidence: 99%
“…Eosinophil progenitors are increased in the blood and sputum of asthmatic patients (65, 66), but their role in disease not fully understood. Intravenous IL-5 increased not only circulating eosinophil progenitors but also CCR3 expression on CD34 + progenitors (67).…”
Section: The Effects Of Il-33 On Mature and Developing Eosinophilsmentioning
confidence: 99%